Metallo-B-iactamase production by pseudomonas aeruginosa of septicemic patients - Ibtesam G. Al grawi; Sabbah A. Belal; Amera K. Al-Abasli (مجلة كلية الطب, 2012)
Background: P. aeruginosa remains a important cause of life threatening bloodstream infection in immunocompromised patients, particularly those with hematologic malignancies complicated by neutropeni.